Effect of Yogic Practices on Heart Rate among College Men Hockey Players - T. , Priya; K. , Murali Rajan (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the present study was to investigate the effect of yogic practices on heart rate among college men hockey players. To achieve the purpose of the study thirty college men students were selected from colleges affiliated to Alagappa University, during the year 2019. The subject’s age ranges from 18 to 24 years. The selected players were divided into two equal groups consists of 15 men students each namely experimental group and control group. The experimental group underwent an yogic practice programme for six weeks. The control group was not taking part in any training during the course of the study. Heart rate was taken as criterion variable in this study. The selected subjects were tested on Heart rate was measured through heart rate monitor. Pre-test was taken before the training period and post- test was measured immediately after the six week training period. Statistical technique‘t’ ratio was used to analyse the means of the pre-test and post test data of experimental group and control group. The results revealed that there was a significant difference found on the criterion variable. The difference is found due to yogic practice given to the experimental group on Heart rate when compared to control group.